2021
DOI: 10.3390/jrfm14120569
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Investor Relations and Good Corporate Governance on Firm Performance in the Case of the Companies Listed on the Bucharest Stock Exchange

Abstract: The objective of this paper is to investigate the role of Investor Relations (IR) in the performance of companies listed on the Bucharest Stock Exchange. The study is motivated by the findings in the literature that investor relations may boost information disclosure, analyst following, institutional investor share, liquidity, and business valuation. The current article contributes to the relevant literature by making use of the recently released unique database of VEKTOR scores on company investor relations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In Iran, Reid et al [2] emphasized the importance of carefully considering regulatory requirements and stakeholder expectations when choosing financial reporting approaches. Mihail et al [3] advocated for strengthening investor relations based on their positive correlation with firm performance. Kartal [4] analyzed the effects of foreign investors on Turkish stock indices, while Katsiaryna et al [5] demonstrated the impact of distraction events on stock return co-movement across different markets.…”
Section: General Studies On the Stock Marketmentioning
confidence: 99%
“…In Iran, Reid et al [2] emphasized the importance of carefully considering regulatory requirements and stakeholder expectations when choosing financial reporting approaches. Mihail et al [3] advocated for strengthening investor relations based on their positive correlation with firm performance. Kartal [4] analyzed the effects of foreign investors on Turkish stock indices, while Katsiaryna et al [5] demonstrated the impact of distraction events on stock return co-movement across different markets.…”
Section: General Studies On the Stock Marketmentioning
confidence: 99%
“…The Social pillar (S) looks at practices towards employees, human rights and equal opportunities to the workforce. Finally, the Governance pillar focuses on the corporate governance structure of the company, which can affect the long-term strategy and value of the company (Mihail et al, 2021). These three pillars should be able to convey information on the "sustainability" of the business (see e.g., Bocken & Short, 2021;Chopra et al, 2021;Jørgensen et al, 2022;Pieroni et al, 2019;Torres, 2021;Wang et al, 2021, among others) and asset allocation process (see e.g., Giese et al, 2019, Gougler and Utz.…”
mentioning
confidence: 99%
“…Standard deviation measures how far a company's stock price deviates from its average price. A small standard deviation indicates low volatility because of the narrow range between its price and average price value (Mihail et al 2021;.…”
mentioning
confidence: 99%